Furniture Design in the Autistic Children's Therapy Room with Ergonomics and Physical Distancing Approaches as an Effort to Prevent the Spread of Covid-19 - Eko Sri Haryanto (Institut Seni Indonesia Surakarta, 2022)
A furniture is an important tool that is used to support the smooth running of teaching and learning activities in schools. The outbreak of covid-19 has made people have to rearrange their distance in interacting so that the spread of covid-19 can be suppressed. This applied research is used to create new designs so that students and therapists can easily access the furniture and feel comfortable when using the furniture. User activities (students and teachers) and ergonomic measurements are very important to see whether the object is to the needs needed by the user, especially for preventing the spread of covid-19.The object of applied research is furniture contained in Special Needs School Autism AGCA Surakarta. The method used in descriptive with a qualitative approach supported by quantitative data can also be called a double research strategy, namely the use of various methods in solving a research problem. The quantififive here uses numerical data which is the result of measurements in the field, then compared with references referenced, sources, and analyzed based on the researcher's interpretation. The results of this applied research are in the form of a new design that can be used as input to the managers of Special Needs School Autistic AGCA Surakarta and similar Special Needs Schools. The results of this applied research are also expected to provide a sifting of course material. ergonomic and Schools. Furniture in the Interior Design Study Program of ISI Surakarta.